Odpowiedzialność nauczyciela akademickiego z tytułu nieprzestrzegania norm etycznych - Nowak, Dominika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Głównym tematem artykułu jest odpowiedzialność nauczyciela akademickiego z tytułu nieprzestrzegania norm etycznych. Analizie zostało poddane zagadnienie odpowiedzialności roli oraz odpowiedzialności wyniku. Stwierdzono, że nauczyciel akademicki ponosi odpowiedzialność roli, jaką pełni w społeczeństwie. Ponadto, w kontekście omawianej problematyki, ponosi odpowiedzialność wyniku z tytułu naruszenia norm etycznych. Takie rozumienie odpowiedzialności najczęściej występuje na gruncie prawnym, gdzie podmiot ponosi określone konsekwencje naruszenia norm prawnych. W związku z powyższym została przedstawiona odpowiedzialność dyscyplinarna, a także karna i cywilna. Całość rozważań prowadzi do odpowiedzi na pytanie, jaki rodzaj odpowiedzialności może zostać przypisany nauczycielom akademickim z tytułu nieprzestrzegania norm etycznych. Badania przeprowadzono opierając się na metodzie formalno-dogmatycznej oraz krytycznej analizy literatury.

The main topic of the article is the responsibility of the academic teacher for failure to comply with ethical standards. The issue of responsibility of the role and responsibility of the result was analyzed. It was found that the academic teacher bears the responsibility for the role he plays in society. In addition, in the context of the issue under discussion, he bears the responsibility of the result for violating ethical norms. This understanding of responsibility is most often found on legal grounds, where the subject bears certain consequences of violating legal norms. In connection with the above, disciplinary responsibility, as well as criminal and civil liability is presented. The entire consideration leads to the question of what kind of responsibility can be attributed to academic teachers for failure to comply with ethical norms. The research was conducted based on the formal-dogmatic method and critical analysis of the literature.
Academic teacher’s responsibility for not complying with ethical standards
Keywords: normy etyczne; nauczyciele akademiccy; szkolnictwo wyższe; odpowiedzialność dyscyplinarna; ethical standards; university teachers; higher education; disciplinary responsibility